2016
DOI: 10.4049/jimmunol.1600094
|View full text |Cite
|
Sign up to set email alerts
|

MMP-25 Metalloprotease Regulates Innate Immune Response through NF-κB Signaling

Abstract: Matrix metalloproteases (MMPs) regulate innate immunity acting over proinflammatory cytokines, chemokines, and other immune-related proteins. MMP-25 (membrane-type 6-MMP) is a membrane-bound enzyme predominantly expressed in leukocytes whose biological function has remained largely unknown. We have generated Mmp25-deficient mice to elucidate the in vivo function of this protease. These mutant mice are viable and fertile and do not show any spontaneous phenotype. However, Mmp25-null mice exhibit a defective inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…P2RY6 has also been implicated in mediating release of pro-inflammatory cytokines and chemokines in monocytes [ 34 ] and macrophages [ 35 ] and promoting vascular inflammation [ 37 ]. MMP25 deficiency has been linked to an defective NF-κB activation and impaired innate immune response in mice [ 38 ]. Future monitoring of these alterations in gene expression, which are linked to inflammatory processes, may offer avenues for regulatory scientists and tobacco companies to measure early toxicity responses to tobacco product use.…”
Section: Discussionmentioning
confidence: 99%
“…P2RY6 has also been implicated in mediating release of pro-inflammatory cytokines and chemokines in monocytes [ 34 ] and macrophages [ 35 ] and promoting vascular inflammation [ 37 ]. MMP25 deficiency has been linked to an defective NF-κB activation and impaired innate immune response in mice [ 38 ]. Future monitoring of these alterations in gene expression, which are linked to inflammatory processes, may offer avenues for regulatory scientists and tobacco companies to measure early toxicity responses to tobacco product use.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Soria-Valles at al. showed that MMP-25 could activate the innate immune response [ 33 ]. Similarly, our study has also found increased transcripts of MMP-8, MMP-9, and MMP-25 in KD, indicating that these proteinases may be potential therapeutic targets for KD.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR2 is a subunit of IL-8 receptor and facilitates IL-8-induced neutrophil chemotaxis while PRG3 has been reported to stimulate neutrophil superoxide production and IL-8 release 25,26 . LBP positively regulates neutrophil response upon LPS stimulation and MMP25 inactivates alpha-1 proteinase inhibitor to facilitate the trans-endothelial migration of neutrophil to inflammatory sites during infection 27,28 . These differentially expressed proteins support a model by which SARS-CoV-2 triggers cytokine release, such as IL-8, in the early stage of infection, resulting in uncontrolled infiltration and activation of neutrophils to the sites of infection followed by eventual progression to cytokine storm and respiratory distress.…”
Section: Global Proteome Profiling Of Pbmcs From Covid-19 Patientsmentioning
confidence: 99%